Los inmigrantes extranjeros en Teruel - Rubio Terrado, Pascual (Geographicalia, 2014)
The arrival of foreign immigrants to the province of Teruel is later than in the whole of Spain, but today, almost all municipalities incorporate foreign population in the population census. The immigration has become the demographic process with the greatest regional impact, in the same way that the emigration was until less than a decade.To know the characteristics of that group of people and their territorial distribution, to evaluate the demographic and territorial arrival and to assess the perception of the immigration process is population Teruel, are the basic objectives of this paper. We start from the premise that when the demographic decline of an area exceeds the capacity of self regenerationof the human group, this becomes a very strong constraint to development, therefore, its functional and human revitalization needs mechanisms that activate a sustained migratory positive balance.